Dosimetric Evaluation of Dose Calculation Uncertainties for MR-Only Approaches in Prostate MR-Guided Radiotherapy - Coric, Ivan; Shreshtha, Kumar; Roque, Thais; Paragios, Nikos; Gani, Cihan; Zips, Daniel; Thorwarth, Daniela; Nachbar, Marcel (Frontiers in Physics, 2022)
Magnetic resonance imaging guided radiotherapy (MRgRT) allows treatment plan adaptation on the MRI of the day. For dose calculations a structure specific bulk relative electron density (RED) overwrite derived from a planning computed tomography (CT) poses as one possible treatment workflow. However, this approach introduces uncertainties due to assignment of mean densities and requires a planning CT. The aim of this study was to investigate the uncertainty of the used patient specific (PSCT) dose calculation in contrast to the correct calculation on a CT and compare to MR-only workflows using population based bulk ED (PBCT) and artificial intelligence-based pseudo-CTs (AICT). Twenty primary prostate cancer patients treated on the 1.5 T MR-Linac were chosen from the clinical database, based on best visual congruence between the planning CT and daily MRI. CT-based reference dose distribution was compared to different pseudo-CT approaches. (1) For PSCT, mean REDs for femur, pelvis, sacrum, rectum, bladder, and patient were assigned based on individual mean CT densities. (2) Population-based mean REDs were derived based on 50 previous, independent patients and assigned to the structures for the PBCT approach. (3) An AI-model for pseudo-CT generation was trained using end-to-end ensembled self-supervised GANs and used to create AICTs from T2w-MRIs. For comparison the CT was registered to the MRI, structures rigidly propagated, and treatment plans recalculated. Differences of DVH-parameters were analyzed, and dose distributions compared using gamma analysis. All approaches were able to reproduce the dose distribution accurately, according to a gamma criterion of 3%/3 mm with pass rates greater than 98%. Applying a 2%/2 mm criterion, the median gamma pass rates for PSCT, PBCT and AICT resulted in 98.6%, 98.2% and 99.0%, respectively. The median differences for PTV D98% resulted in 0.13Gy for AICT, -0.31Gy for PBCT and -0.32Gy for PSCT. OAR related DVH parameter showed similar results between the three investigated methods. In this study, a detailed analysis of uncertainties of MR-only treatment planning concepts for pelvic MRgRT was performed. Both, a PBCT and AICT approach, which bypass the need for a planning CT may be considered clinically acceptable whilst reducing imaging dose and registration issues.